On the solution of a system of integral equations via matrix version of Banach contraction principle - Ali, Muhammad Usman; Kamran, Tayyab; Houmani, Hassan; Postolache, Mihai (Communications in Mathematics and Applications, 2017)
The purpose of this paper is to extend Perov's fixed point theorem in the setting of  modular generalized metric space, which is also establish in this article. Further we discuss the Perov's result in the setting of two modular generalized metric spaes. As an application we prove the existence of solution for a system of integral equations.
Keywords: Generalized metric space; modular generalized metric space; modular metric space